PENERJEMAHAN NOMENKLATUR RESMI DI MAHKAMAH AGUNG: ANALISIS KESEPADANAN DAN TANTANGANNYA - Nugroho, Agus Digdo Nugroho; Johanes, Johanes (Kementerian Sekretariat Negara Republik Indonesia, 2025)
This study examines the translation practices of official nomenclature related to institutions, positions, and organizational units within the Supreme Court of the Republic of Indonesia and its subordinate judicial bodies. Employing a qualitative descriptive approach through document analysis and case studies, this research identifies frequent translation errors and inconsistencies found in official documents and international correspondence. Findings reveal that many translations fail to reflect the civil law system adopted in Indonesia, often using terms derived from common law traditions, such as “clerk” instead of “registrar” or “chairman” instead of “chief judge.” These inaccuracies not only undermine the institutional meaning and authority of the translated terms but also risk miscommunication and reduced credibility in international judicial cooperation. The study highlights the need for systemic equivalence, cross-cultural readability, and international acceptability in legal translation. It recommends the development of standardized English nomenclature through interdisciplinary collaboration among linguists, legal experts, and legal translators. Establishing official translation guidelines is deemed essential to ensure consistency, clarity, and professionalism in cross-border judicial communication. The implications of this research underscore the importance of accurate legal translation for institutional identity, legal transparency, and international engagement.